AGE-RELATED CHANGES IN OVARIAN ENDOMETRIOSIS MORPHOLOGY (American Journal of Interdisciplinary Research and Development, 2024)
Uterine endometriosis is a disease associated with the growth of endometrial tissue in the inner lining of the uterus outside the uterus. This pathology occurs in many women and can seriously affect their reproductive health. The morphologic features of endometriosis include age-related aspects, which affect disease progression, symptomatology, and treatment strategies.